1994
DOI: 10.1288/00005537-199403000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive optical diagnosis of bacteria causing otitis media

Abstract: Currently, the identification of the bacteria responsible for acute otitis media requires a painful invasive procedure: tympanocentesis. To develop a rapid and noninvasive technique for bacterial diagnosis, the fluorescence profiles of four common pathogens and the optical characteristics of the tympanic membrane have been investigated. Each bacterium produces a unique in vitro fluorescence profile when measured in a saline suspension. Also, spectrally resolved transmission measurements from the chinchilla tym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…First, we (Pinnick et al, 1995) and others (Hairston et al, 1997) have shown that fluorescence particle counters that measure the elastic scattering and total (undisperscd) fluorescence can differentiate between some bioloeical " and nonbiological aerosols; the advantage of obtaining single-particle measurements (as opposed to volumc scattering measurements on many particles) are cited above. Second, excitation/emission spectra of the intrinsic fluorescence of biological particles have been shown to be useful for differentiating between a few types of biological (Sorrel1 et al, 1994;Werkhaven et al, 1994). These spectra and similar more extensive excitation/emission spectra measured for a number of microorganisms in liquid suspension (Steve Gotoff, private communication March 1997) suggest that excitation with multiple wavelengths will be necessary for more-than a mostrudimentary classification.…”
Section: Introductionmentioning
confidence: 96%
“…First, we (Pinnick et al, 1995) and others (Hairston et al, 1997) have shown that fluorescence particle counters that measure the elastic scattering and total (undisperscd) fluorescence can differentiate between some bioloeical " and nonbiological aerosols; the advantage of obtaining single-particle measurements (as opposed to volumc scattering measurements on many particles) are cited above. Second, excitation/emission spectra of the intrinsic fluorescence of biological particles have been shown to be useful for differentiating between a few types of biological (Sorrel1 et al, 1994;Werkhaven et al, 1994). These spectra and similar more extensive excitation/emission spectra measured for a number of microorganisms in liquid suspension (Steve Gotoff, private communication March 1997) suggest that excitation with multiple wavelengths will be necessary for more-than a mostrudimentary classification.…”
Section: Introductionmentioning
confidence: 96%
“…Werkhaven et al 2 acknowledged the potential for the tympanic membrane to create its own fluorescence signal and absorb a portion of the excitation and emission wavelengths in vivo. Thus they measured the emission pattern and absorption spectrum of a tympanic membrane from a healthy animal in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by Werkhaven et al 2 and Sorrell et al 3 has established the groundwork for accurate identification of common bacterial pathogens using fluorescence emission spectroscopy. In their investigation, S pneumoniae , H influenzae , M catarrhalis , and Staphylococcus aureus were each suspended in saline, placed in a quartz cuvette, and successively differentiated in vitro by analysis of their emission spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Native fluorescence from bacteria in the visible and UV is dominated by tryptophan emission. [1][2][3][4][5][6] Emission in the 430-to 514-nm region from pterins, nicotinamide adenine dinucleotide, nicotinamide adenine dinucleotide phosphate, and flavin adenine dinucleotides have also been observed. 3 The development of bacterial endospores by Bacillus subtilis ͑Bs͒ represents one of the best-studied models for the observation of the well-defined process of spore formation.…”
Section: Introductionmentioning
confidence: 94%